TLR2/TLR4-Enhanced TIPE2 Expression Is Involved in Post-Hemorrhagic Shock Mesenteric Lymph-Induced Activation of CD4+T Cells - Du, Hui-Bo; Jiang, Sun-Ban; Zhao, Zhen-Ao; Zhang, Hong; Zhang, Li-Min; Wang, Zhao; Guo, Ya-Xiong; Zhai, Jia-Yi; Wang, Peng; Zhao, Zi-Gang; Niu, Chun-Yu; Jiang, Li-Na (Frontiers in Immunology, 2022)
Purpose: Post hemorrhagic shock mesenteric lymph (PHSML) return contributes to CD4+ T cell dysfunction, which leads to immune dysfunction and uncontrolled inflammatory response. Tumor necrosis factor α induced protein 8 like-2 (TIPE2) is one of the essential proteins to maintain the immune homeostasis. This study investigated the role of TIPE2 in regulation of CD4+ T lymphocyte function in interaction of PHSML and TLR2/TLR4. Methods: The splenic CD4+ T cells were isolated from various mice (WT, TLR2-/-, TLR4-/-) by immunomagnetic beads, and stimulated with PHSML, normal lymphatic fluid (NML), respectively. Application of TIPE2-carrying interfering fragments of lentivirus were transfected to WT, TLR4-/-, and TLR2-/- CD4+ T cells, respectively. After interference of TIPE2, they were stimulated with PHSML and NML for the examinations of TIPE2, TLR2, and TLR4 mRNA expressions, proliferation, activation molecules on surface, and cytokine secretion function. Results: PHSML stimulation significantly upregulated TIPE2, TLR2, and TLR4 mRNA expressions, decreased proliferation, CD25 expression, and IFN-γ secretion, and increased the secretion ability of IL-4 in WT CD4+ T cells. TIPE2 silencing enhanced proliferative capacity, upregulated CD25 expression, and increased IFNγ secretion in CD4+ T cells. PHSML stimulated TLR2-/-CD4+ T or TLR4-/-CD4+ T cells of which TIPE2 were silenced. TLR2 or TLR4 knockout attenuated PHSML-induced CD4+ T cells dysfunction; PHSML stimulation of silent TIPE2-expressing TLR2-/-CD4+ T or TLR4-/-CD4+ T revealed that the coexistence of low TIPE2 expression with lack of TLR2 or TLR4 eliminated this beneficial effect. Conclusion: TIPE2 improves the PHSML-mediated CD4+T cells dysfunction by regulating TLR2/TLR4 pathway, providing a new intervention target following hemorrhagic shock-induced immune dysfunction.